Kesulitan Siswa dalam Pemecahan Masalah Soal Cerita Matematika Dilihat dari Adversity Quotient (AQ) - Bruno, Antonius; Qohar, Abd.; Susanto, Hery; Permadi, Hendro (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
Problem solving is one of the main goals in learning mathematics and can be realized in solving story problems. The purpose of this study is to describe the difficulties of climbers, campers and quitters' students in solving mathematical problems in the form of story questions based on Polya's steps. This research uses qualitative research with a case study approach design. The instrument is the researcher himself and the supporting instruments are questionnaires, problem solving test instruments and interviews. The population in this study were students of SMPK Mardi Wiyata Malang class VIII B which were taken 6 subjects (2 Climber students, 2 Camper students and 2 Quitter students) based on the results of Adversity Response Profile (ARP) questionnaire data. The results in this study consist of the difficulty of climber students in solving problem solving, namely the difficulty in solving problems and making conclusions from the problems that have been solved. Camper students' difficulties in solving problem solving are difficulties in planning problem solving strategies, problems solving and drawing conclusions from the problems given. The difficulty of quitter students in solving problem solving is the difficulty of students in understanding problems, planning solutions, making solutions and drawing conclusions from the problems given. Based on the findings, students with the quitter category have the lowest ability in the problem-solving process. Therefore, further research is needed to increase the motivation and interest in learning of students belonging to the quitter category.